Metabolic Interaction in Infection (Experientia Supplementum,, 2018)
This book focuses on host-pathogen interactions at the metabolic level. It explores the metabolic requirements of the infectious agents, the microbial metabolic pathways that are dedicated to circumvent host immune mechanisms as well as the molecular mechanisms by which pathogens hijack host cell metabolism for their own benefit. Finally, it provides insights on the possible clinical and immunotherapeutic applications, as well as on the available experimental and analytical methods. The contributions break new ground in understanding the metabolic crosstalk between host and pathogen.